Effect of seed moisture content at harvesting time on seed germinability of two oilseed rape (Brassica napus L.) cultivars in Dezfoul region - حسین صادقی; مهران شرفی زاده; ویکتوریا عسکری (علوم و فناوری بذر ایران, 2012)
In order to evaluation of moisture content at harvesting of two Oilseed Rape(Brassica napus L.) a study was conducted in 2007- 2009 in Dezfoul region. Therefore, samples of Hyola 401 and Hyola 308 seeds at 10, 15, 25 and 35% moisture content at harvest were taken from the field in Dezfoul and tested at the seed analysis laboratory. Some seed quality indices like primary and final germination percentage (seed viability) and daily germination speed (DGS) were measured. Data obtained using a 2andtimes;4 factorial experimental based on a completely randomized design with three replications, combined analysis revealed that primary and final germination percentage affected by cultivar andtimes; seed moisture content andtimes; year interaction and daily germination speed affected by cultivar andtimes; seed moisture content interaction. The highest primary and final germination at 15% seed moisture content and and daily germination speed in seeds with 10 and 15% moisture content was more than seeds with 25 and 35% moisture content. In addition, primary and final germination percentage of Hyola 401 was higher than Hyola 308. These results revealed that seed quality was affected by environmental factors and seeds harvested at 15% moisture content showed the highest quality.